THE DIDACTIC FEATURES OF GRAPHIC PREPARATION OF FUTURE EDUCATORS IN PROFESSIONAL AND TECHNOLOGICAL EDUCATION IN THE MOODLE DISTANCE LEARNING SYSTEM - Гедзик, Андрій (SWorldJournal, 2024)
The paper delves into the promising avenues of leveraging information technologies within the educational realm, specifically focusing on the professional and technological education of future educators. Through platforms such as the Moodle distance learn